THERMO-MECHANICAL PHENOMENA IN THE SURFACE LAYERS OF CONTACTING PARTS DURING FRICTION AND WEAR - Malinovskiy, Yuriy; Tsvirkun, Sergij; Vlasenkov, Dmitro; Oliinyk, Svitlana (Problems of Friction and Wear, 2023)
Despite a significant number of theories of friction and wear, the issue of wave formation on contacting surfaces and in the zone ahead of the moving part has not yet received a sufficiently deep justification. Based on accumulated theoretical and experimental data, it is generally accepted to consider the groups of theories: 1) geometric, 2) molecular (adhesive), 3) deformation, 4) combined [1]. The most widespread opinion is that friction is caused by plastic extrusion of the material and the destruction of welding bridges (F. R. Bowden and D. Tabor), which is also confirmed by the hypothesis of Ernst and Margent, where friction is caused by adhesion (at the molecular level and surface roughness). At the same time, the experimental results of F. R. Bowden and D. Tabor indicate that the effect of friction depends on both the adhesion forces and the deformation of the material in the thin surface layer. As a result of the application of significant compressive forces and tangential frictional forces, a large amount of energy is released at the contact of two bodies, and with weak heat exchange with the environment, high gradients of temperature changes occur, and in the case of metal parts, under certain conditions, the welding effect of both individual micro-uniformities and contact surfaces in general, which is confirmed by research results [2].